Appointment Management System for Elvira True Beauty Salon with Two-Factor Authentication - Yeap, Alise Rou Xin; Mohd Foozy, Cik Feresa (Applied Information Technology And Computer Science, 2024)
Elvira True Beauty Salon currently relies on manual appointment management, which had leading to inconvenience and ineffectiveness of appointment management, human error during the appointment management, and security concerns such as data breaches and information leakage. This project aims to address these issues by developing a secure online appointment management system for the salon. The developed system was intended for salon owners, staff (beauticians), and customers. In the system, Two-Factor Authentication (2FA) with strong passwords, One-Time Passwords (OTPs) via WhatsApp, and a zero-trust principle with security questions was implemented. Meanwhile, HTML, CSS, and JavaScript were applied for the front-end, while PHP with MySQL for the backend. In the system development, System Development Life Cycle (SDLC) Prototyping Model was used as guidance. Lastly, the developed system was tested by 5 respondents. By the end of this project, an efficient solution to replace the salon's manual process, ensuring enhanced security and streamlined appointment management was developed.